Analysis of Development Planning for Infrastructure with Land Consolidation Concept in the Mandalika Special Economic Zone (SEZ) - Baiq Elny Susanti; Ngudiyono Ngudiyono; Muhajirah Muhajirah (Litbang Pemas - Universitas Islam Lamongan, 2022)
Mandalika Special Economic Zone (SEZ) a national priority super tourism destination. The plan for holding an international MotoGP event requires the preparation of supporting infrastructure development. One of the pressing issues needing resolution is land conditions for permanent relocation. From a technical point of view, the land is still in the form of terracing, road access to the location is heavily damaged and some of the roads are unpaved. In addition, the relocation settlement area does not yet have public infrastructure. In this study sought to determine a strategy of funding sources for infrastructure development as well as priority factors for planning the development of infrastructure with the concept of land consolidation. The analysis in this study was carried out using Analytical Hierarchy Process (AHP) technique, showing that environmental factors had the highest weight of 0.414, followed by infrastructural with 0.295, economy with 0.157 and social factors with 0.133. For alternative factors, accessibility had a weight of 0.167, price had a weight of 0.148, quality had a weight of 0.161, location had a weight of 0.201, infrastructure had a weight of 0.176 and tradition had a weight of 0.144.